PENGARUH METODE INQUIRI TERPIMPIN DALAM PEMBELAJARAN BIOLOGI TERHADAP KETERAMPILAN PROSES SAINS DITINJAU DARI MINAT BELAJAR SISWA SMA TAHUN PELAJARAN 2011/2012 - Agustin, Putri Sartika; Probosari, Riezky Maya; Harlita, Harlita (Pendidikan Biologi, 2011)
ABSTRACT ? The purposes of this research were to know: 1) the influence of guided inquiry method to the science process skills; 2) the influence of student?s learning interest to science process skills; 3) the interaction between learning method and learning interest to the science process skills. This research was quasi experiment research using Randomized Control Only design. Learning method and learning interest were independent variables and to science process skills was the dependent variable. The population of this research was all of  XI grade of natural science students of SMA Negeri 1 Boyolali. The samples of this research were the students of class XI IPA 2 as the experimental group and students of class XI IPA 6 as the control group.  The sample of this research was established by cluster random sampling. The data about science process skills collected by use observation. Learning interest measured by observation. The analysis was anava two away in different cell and the advance test used Bonfferoni test. The conclusion of this research were: 1) Guided Inquiry method had significant influence to science process skills on XI grade of SMA Negeri 1 Boyolali; 2) Learning interest had significant influence to science process skills on XI grade of SMA Negeri 1 Boyolali; 3) There wasn?t interaction between learning method and learning interest to science process skills on XI grade of SMA Negeri 1 Boyolali. Keywords: Science Process Skills, Guided Inquiry Method, and learning Interest